Die devitaliseringsdialektiek van die skool: enkele fundamentele probleme - Villiers, J. H. de (Koers, 1992)
Historically the school has been subject to a de-/vitalizing power-play fulfilled through the manipulative power of holders of power under the primacy of a specific religious ground motif The result has been that the school is seemingly experiencing an identity crisis because of the incomplete definition of its task of educative teaching, because man/power-holders have historically been wont to regard himself/themselves as the justified determiner of meaning of his/their structures. Subsequently the school's foundational function, its destinational function and its sphere of competence have been defined by way of apostatic ground motifs and secular points of departure. Thus the school has been subjected to a never-ending, self-denying bipolar play of power which can be self-undermining. While no power-play can be driven to its fullest consequences, 1school reforms* have been self-abortive in nature. There is therefore the demand to provide the school with a stable value system which for the Christian is situated in the creation-fall-redemption religious ground motif which places man in a radical Creator-creature relationship.